Fatores que influenciam o papel do orquestrador de ecossistema de inovação no segmento de saúde privada no Brasil - Alves, Carla Viana (2024)
This doctoral thesis investigates the factors influencing the role of the leader of the innovation ecosystem concerning private healthcare sector in Brazil. Despite their importance in daily reality in Health, it is unrealistic to assume that the factors influencing the innovation ecosystem are entirely known, a shortcoming this work addresses. Based on the Stakeholder Theory using qualitative research, including semi-structured, in-depth interviews with experts in the sector, this study aims to build the limited previous works that analyzed the Innovation Ecosystem Orchestration. After careful content, cluster, and thematic analysis, ten themes (factors) emerged: (a) Creativity; (b) Strategic Thinking; (c) Leadership; (d) Resilience; (e) Compliance; (f) Social Transformation; (g) Connections; (h) Teaching; (i) Mastery of Technologies and Trends and (j) Intrapreneurship. This work contributes theoretically to the Stakeholder Theory, explaining how stakeholders can change organizational spheres through creativity, strategic thinking, leadership, resilience, networking, entrepreneurship, and Mastering Technology and Tendencies. Just like compliance presents a new legitimacy for stakeholders about the organization they belong to, and social transformation and institutional challenges offer new nuances to the urgency of providing services to recognized organizational revindication. This research is transferable to other sectors, such as the relationship between the government and NGOs, educational institutions, international organizations, political organizations, cooperatives, and partnerships. The conclusion of this work supports the idea that these factors should foster best practices regarding value creation in innovation ecosystem scenarios. This work is helpful to decision-makers, scholars, and other practitioners. The study’s significance sets the grounds for future research in the area. It would assist decision-makers in better understanding how to foster the innovation ecosystem within the organizations. Finally, implications and discussions comprise this research.